Customer Loyalty Analysis with Markov Chain and Customer Bonding Strategy: Case Study at PT XYZ - Anwar, Balqis; Lahay, Idham Halid; Uloli, Hendra (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2026)
Thiis stiudy aiims to analyze customer loyalty at PT XYZ is using the Markov Chain approach and Customer Bonding strategy. The research method combines quantitative analysis through Markov Chain to predict customer switching and qualitative analysis through questionnaires to measure the effectiveness of the Customer Bonding strategy. The results showed that the probability of customers staying was 54%, while the probability of moving to competitors was 46%. The Customer Bonding strategy, especially in the aspects of relationship bonding and advocacy bonding, has proven effective in increasing customer loyalty. The strategies that can be carried out so that XYZ Workshop does not experience a drastic decline in customers are by implementing strategies such as: Customer Retention Strategy, Improving Quality and Differentiation, Expanding Market Access, and Reanalyzing Business Models. However, the availability of spare parts and product design are still weaknesses that need to be improved.This study provides practical implications for companies in designing more effective customer retention strategies.